Human senescent phenotypes - Arking, Robert (Henry Stewart Talks, 2016)
Life phases and human senescent phenotypes, Seven major human senescence phenotypes, Hypertension, Atherosclerosis, Alzheimer’s disease, Diabetes type 2, Muscle aging, Gastrointestinal cancers, Skin aging, Inflammasomes and aging